PERSPEKTIF PETANI TERHADAP ASPEK SOSIAL PERTANIAN BERKELANJUTAN DI KABUPATEN KULON PROGO - Dyah Woro Untari; Sri Peni Wastutiningsih (Agro Ekonomi, 2010)
The objectives of this study are to investigate fanner's perspective on sustainable agriculture social aspect: (1) Socially just agricultural system principle and (2) culturally appropriate principle. The total sample was 60 farmers, 30 farmers were selected from wetland ecosystem and another 30 farmers were selected from coastal ecosystem. Those 60 samples were taken by simple random sampling method Three ways analysis qualitative data used in analyzing the data. The result shows, on socially just agricultural system principle, there are 1,67% farmers have low comprehension on social indicator, membership in organization indicator, credit support service indicator, information and training support services indicator and family participation indicator. There are 6,67% farmers have a low comprehension on food security indicator. There are 51,67% farmers stated comprehension on postharvest facility support service indicator. On culturally appropriate principle, local wisdom for farming support comprehends by 50,00% farmers.